KOMUNIKASI PERSUASIF MEDIATOR DALAM PERKARA PERCERAIAN DI PENGADILAN AGAMA BANGKINANG - Nirmala Osela; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Divorce cases are not new to people's lives. Over time, various problems arise in a domestic relationship. Religious justice becomes the last solution when the meeting point of the problem never gets. Based on data obtained from the Clerk of the Bangkinang Religious Court, in 2018 there were 1197 cases that were entered and processed. divorce is in first place with 749 cases, then followed by divorce as many as 321 cases. In 2018 out of 223 cases mediated, only 6 cases were successfully mediated. In practice, mediators at the Bangkinang Religious Court used persuasive communication techniques that were expected to touch hearts and feelings for both parties who were litigating.               This study uses descriptive qualitative research methods with a persuasive communication model by Applebaum and Anatol. The object of research in this research is how the mediator's persuasive communication process in the Bangkinang Religious Court in an effort to reduce the divorce rate and how the persuasive communication model used by the mediator in the Bangkinang Religious Court. The data analysis technique used in this study is the qualitative data analysis technique of the Miles and Huberman models.               The results showed that the mediation process in the Bangkinang Religious Court was not necessarily carried out in all cases, the various stages of the lawsuit request made, processed, tried, mediated and decided were very long and winding. The persuasive communication efforts and approaches used by the mediator of the Bangkinang religious court in activities mediation begins by giving a good first impression of the mediator to both parties, after that the mediator also seeks to eliminate the distance and boundaries with both parties, after which the mediator will open access to communication with both parties, when access to communication has been created, the steps then the mediator will deliver a persuasive message in accordance with the problems that are befalling both parties, the final stage is that the mediator will provide an opportunity for both parties to respond to the message. From the author's observations, the persuasive efforts made are maximized as well as the communication model used. Various messages and advice given to the plaintiff and the defendant were constrained because the intention to separate was very unanimous.